KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA DALAM MENYELESAIKAN SOAL BANGUN DATAR DITINJAU DARI SELF-REGULATED LEARNING - Nur Irsa Hadayana; Ade Mirza; Hamdani Hamdani; Revi Lestari Pasaribu (Jurnal Education and Development, 2023)
The research purpose is to find out the mathematically creative thinking skills in terms of Self-regulated learning to finish the plane figure questions. The methodology of research used qualitative descriptive design. The research participant consists of 12 seventh-grade students of Junior High School 10 in Pontianak. The result of the research was researcher found that students have high creative thinking skills. Students could finish plane figure questions correctly and fluently from a variety of points of view and the new and unique answers, students also could self-regulate when deciding the purpose and target of learning or fulfill three indicators of creative thinking skills, such as fluency, flexibility and novelty. Students have medium-high creative thinking skills with self-regulated learning. Students could finish the plane figure questions correctly and fluently from a variety of points of view but they could not give new answers or just fulfill two indicators of creative thinking skills, such as fluency and flexibility. While students have low creative thinking skills with Self-regulated learning. Students could not fulfill three indicators of creative thinking skills. Students could not self-regulate when deciding the purpose and target of learning.